Reality Group Counseling to Improving Self-Esteem of Students - Puluhulawa, Meiske; Djibran, Moh. Rizki; Pautina, Mohamad Rizal (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2017)
Reality group counseling is a short-term therapy that focuses on the present moment, emphasizes personal power, and on the dasamya is the way in which the members of the group can learn behaviors and more realistic. Group counseling activities of reality can also make its members better appreciate opinions of others, and bolder posited opinion are responsible for developing self esteem with eight stages as follows: (1) counselor demonstrated involvement with konseli (be friend), (2) focus on the behavior now, (3) explore the total behavior konseli, (4) konseli judge for yourself or do evaluation, (5) the responsible action plan, (6) make commitment, (7) receive no apology or excuse konseli, (8) follow-up. self esteem is individual assessment against him, describing the extent to which the individual assess her as a person who has the ability, keberartian, valuable, and competent.